2022
DOI: 10.3389/fped.2022.896903
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: MIS-C With Prominent Hepatic and Pancreatic Involvement in a Vaccinated Adolescent – A Critical Reasoning

Abstract: Multisystem inflammatory syndrome in children (MIS-C) is a pathologic condition that has emerged during the coronavirus disease 2019 (COVID-19) pandemic. Although the epidemiological evidence of association between MIS-C and SARS-CoV-2 infection has been demonstrated, its pathogenic mechanism is still undefined. We describe the case of a 17-year old female, previously vaccinated against SARS-CoV-2, presenting with a history of asthenia, fever, cough, anorexia, abdominal pain, and vomiting. During the hospitali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…A report by CDC has highlighted that immunological protection of the COVID vaccine declines 6–8 months following vaccination and different studies have also raised concern about the long effectiveness of the COVID vaccine ( 120 ). Since there is uncertainty about the long-term protective effect of the COVID-19 vaccine, exposing the children will not be a wise decision.…”
Section: Discussionmentioning
confidence: 99%
“…A report by CDC has highlighted that immunological protection of the COVID vaccine declines 6–8 months following vaccination and different studies have also raised concern about the long effectiveness of the COVID vaccine ( 120 ). Since there is uncertainty about the long-term protective effect of the COVID-19 vaccine, exposing the children will not be a wise decision.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Jain et al [ 22 ] and Collignon et al [ 23 ] reported cases with a short interval between vaccination and PIMS-TS symptoms, suggesting other factors at play. Similarly, cases reported by Consollini et al [ 24 ], Salzman et al [ 25 ], and DeJong et al [ 26 ] involved prior SARS-CoV-2 exposure, complicating the causal link to vaccination. In another case, Lee et al described a child who developed PIMS-TS MIS-C after being exposed to COVID-19 despite the vaccination [ 27 ].…”
Section: Discussion and Literature Reviewmentioning
confidence: 94%
“…Four patients received ASA as antiaggregant therapy for the increased risk of thrombotic events [101,[110][111][112]. One patient started anticoagulant therapy (heparin) due to the concomitant contraceptive therapy [103]. All vaccine-related MIS-C patients clinically improved and fully recovered without sequalae.…”
Section: Sars-cov-2 Vaccination-related Mis-cmentioning
confidence: 99%